THE IMPORTANCE OF ADDITIONAL MID SWING TOE CLEARANCE FOR AMPUTEES - Lechler Knut; Kristjansson Kristleifur (Canadian Prosthetics & Orthotics Journal, 2018)
Abstract Increased prosthetic hip to toe distance and insufficient mid swing toe clearance of a prosthetic foot is a well-recognized inadequacy for lower limb prosthesis users with wide and possible grave consequences on their ambulation capabilities. Most important are increased risk of falls and abnormal compensatory gait patterns with secondary unwanted physical effect like generally deceased mobility, muscular-skeletal pain and joint degeneration, i.e. osteoarthritis, with possible significant health economic effect. Even though insufficient toe clearance can be device related and technically or even intentionally induced for attaining equal length of the lower extremities in a neutral standing position or the stance phase, it is important to be aware of available technical solutions that can counteract the problem, like swing phase dorsiflexing feet, vacuum suspension systems, polycentric axis knees rather than single-axis knees and adequate knee flexion in early swing and swing-flexion assistance in the case of bionic knees. Article PDf Link: https://jps.library.utoronto.ca/index.php/cpoj/article/view/30813/23259 How to cite: Lechler K, and Kristjansson K. The importance of additional mid swing toe clearance for amputees. Canadian Prosthetics & Orthotics Journal. Volume1, Issue2, No.1, 2018. DOI: https://doi.org/10.33137/cpoj.v1i2.30813 Authors Biographies: Mr. Knut Lechler, Össur Medical Director Prosthetics, is a CPO-D at Ossur ehf, Reykjavik, Iceland and has been in that position for 7 years. He graduated in 1991 as CPO (Master) and used to work as a freelancer before he started in the industry in 1999 (Flex-Foot Inc.). Since 2001 he is with Össur. Knut Lechler is an active member of the ISO-TC 168 WG1 Kristleifur Kristjansson, Össur Medical Office, R&D Össur ehf, Reykjavik, Iceland. Dr. Kristleifur Kristjansson, Medical Officer and VP of Clinical Affairs, is a medical doctor and has been in his current position at Össur for 6 years. Dr. Kristjansson was a VP of Clinical Collaborations at ...